Novel chlorine resistant low-fouling ultrafiltration membrane based on a hydrophilic polyaniline derivative. Issue 16 (28th April 2015) - Huang, Xinwei; McVerry, Brian T.; Marambio-Jones, Catalina; Wong, Mavis C. Y.; Hoek, Eric M. V.; Kaner, Richard B.
<x xml:space="preserve">Abstract</x> n-PANi, an outstanding candidate for making chlorine tolerant antifouling ultrafiltration membranes.